Pendukung Keputusan Dengan Perbandingan Metode WASPAS dan Metode MAUT pada Pemilihan Karyawan Baru - Ilham, Safarul (Jurnal Sains dan Teknologi Informasi, 2025)
In searching for employee candidates who meet the desired criteria, a solution is needed to select prospective employees. The solution that can be done is to create a decision support system to simplify the process of selecting employee files that have been received. Decision Support Systems (DSS) that can help companies to select prospective employees who register using the comparison of the Weight Aggregated Sum Product Assessment (WASPAS) method is a combination of the WP and SAW methods, where the WP method is a method that uses multiplication in connecting the value of each attribute that must previously be raised to the power of the attribute's weighted value, while the SAW method is generally known as a weighted sum that focuses on calculating the sum of the weighted values ​​of alternative criteria, with the Multi-Utility Attribute Theory (MAUT) method being a quantitative method that is used as a basis for decision making through systematic procedures that identify and analyze several variables. In its application, the decision support system, comparing the WASPAS and MAUT methods in selecting prospective employees according to the given criteria, yielded alternative A5, but with different scores. The WASPAS method scored alternative A5 at 0.890, while the MAUT method scored 0.875.